2010
DOI: 10.1097/tme.0b013e3181f91aed
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Nurse Practitioners and Physician Assistants in Washington and Oregon Emergency Departments

Abstract: Crowding in emergency departments is threatening the quality and safety of care. Use of nurse practitioners and physician assistants in this setting may be a cost-effective model, but there is little data on how to effectively utilize these providers. The purpose of this research was to determine utilization and current staffing patterns of nurse practitioners and physician assistants in emergency departments. Managers in Washington and Oregon emergency departments were surveyed in March 2009. There was a 59% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Finally, we again turn our attention to the personal experience of the remote NP, who is often under pressure to learn and perform EPSs with minimal oversight and support. As cited by multiple studies (Abbot et al, 2010; Barnes et al, 2018; Brown et al, 2009; Laustsen, 2013; Lawler & Valand, 1988; Owens, 2018; Spetz, Skillman, & Andrilla, 2017), although the experience of the isolated NPs performing procedures has driven some research, it is critical that their personal experience continues to be included as a data source for quality improvement and research moving forward. It will be imperative to continue to survey the personal experience of these NPs after they have completed training programs such as the RAST-NP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we again turn our attention to the personal experience of the remote NP, who is often under pressure to learn and perform EPSs with minimal oversight and support. As cited by multiple studies (Abbot et al, 2010; Barnes et al, 2018; Brown et al, 2009; Laustsen, 2013; Lawler & Valand, 1988; Owens, 2018; Spetz, Skillman, & Andrilla, 2017), although the experience of the isolated NPs performing procedures has driven some research, it is critical that their personal experience continues to be included as a data source for quality improvement and research moving forward. It will be imperative to continue to survey the personal experience of these NPs after they have completed training programs such as the RAST-NP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Morgan and Calleja's thorough review in 2020 also found that “non-trauma centers can effectively treat trauma patients in some studies with no difference in mortality” (p. 4) if the providers have adequate training. Nurse practitioners serving these areas require a wider scope of emergency procedural skills (EPSs) to better meet the needs of their isolated residents, often needing to utilize more advanced skills for more acute care scenarios (Abbott, Schepp, Zierler, & Ward, 2010; Brown, Hart, & Burman, 2009). Laustsen (2013) surveyed primary care NPs in Oregon concerning advanced clinical and procedural skills and found that the majority of NPs reported that they did not learn these skills in their NP educational program, but rather “on the job,” often in more remote settings with minimal physician collaboration (p. 39).…”
mentioning
confidence: 99%
“…Advanced practice providers were responsible for executing the plans for treatment and disposition of CCSU patients, which included coordination of care with the ED critical care physicians, consultants, nursing, and ancillary staff; performing procedures (eg, lumbar punctures, incision and drainage of abscesses, suturing lacerations); arranging for, reviewing the results of, and responding appropriately to laboratory testing and radiologic imaging; continuously re‐evaluating each patient's medical condition and needs; communicating with family and outpatient care providers; arranging follow‐up and future care; and providing discharge instructions and patient education. This advanced practice provider‐staffed CCSU reflects the practice of other EDs in exploring and expanding the roles advanced practice providers play in ED clinical care, as well as calls for more formal analyses of these roles 1‐7 . Although initiatives such as the CCSU appear to be promising, their value needs formal assessment before they can be recommended for implementation elsewhere.…”
Section: Introductionmentioning
confidence: 99%